Marketing communication strategy in increasing sales of pottery products - Indah Permatasari; Hendri Hermawan Adinugraha (Indonesian Journal of Islamic Economics Research, 2021)
The Pottery industry sector has become a side and even main livelihood for certain people. However, changing times to a more modern era has made pottery products rarely used. It is necessary to apply the right marketing strategy so that pottery products still exist and can develop, one of which is through marketing communications. Through marketing communication is expected to increase product sales. The purpose of this study was to find out how the marketing communication strategy in increasing sales of pottery products. The research method used is qualitative through a literature study approach. Good and effective marketing communication can be a strategy for craftsmen to increase sales of pottery products. Marketing activities for pottery products are carried out by prioritizing raw materials for making pottery craftsmen themselves, so that they can know the process of making pottery craft, determining process, marketing locations or place, and promotion process